Real-time Colorized Video Images Optimization Method in Scotopic Vision - Chen Yong; Shuai Feng; Zhan Di (Institute of Advanced Engineering and Science, 2015)
In low light environment, the surveillance video image has lower contrast，less information and uneven brightness. To solve this problem, this paper puts forward a contrast resolution compensation algorithm based on human visual perception model. It extracts Y component from the YUV video image acquired by camera originally to subtract contrast feature parameters, then makes a proportional integral type contrast resolution compensation for low light pixels in Y component and makes index contrast resolution compensation for high light pixels adaptively to enhance brightness of the video image while maintains the U and V components. Then it compresses the video images and transmits them via internet. Finally, it decodes and displays the video image on the device of intelligent surveillance system. The experimental results show that, the algorithm can effectively improve the contrast resolution of the video image and maintain the color of video image well. It also can meet the real-time requirement of video monitoring.